Layer by Layer Segmentation of Water Distribution from Neutron Imaging of Large Scale Cells. Issue 6 (1st January 2015) - Boillat, Pierre; Iranzo, Alfredo; Biesdorf, Johannes
Abstract : We present a method for distinguishing liquid water content in the different layers of a polymer electrolyte fuel cell ("anode flow channels", "cathode flow channels", and "GDL/MEA") from through-plane neutron imaging. The method is based on sudden decompression of the anode and cathode sides of a cell in two separate steps. The decompression induces a strong purging effect with effective liquid water removal from the flow channels, without affecting the gas diffusion layers (GDL) and membrane electrode assembly (MEA). The water in the flow channels is imaged by the differences of water distribution before and after the corresponding purges, and the water remaining after the purges is considered to be GDL/MEA water. The method is valid both for qualitative and quantitative analysis. A validation of the method is presented in this work, including results obtained for a 50 cm 2 commercial PEFC.